1993
DOI: 10.1002/pca.2800040602
|View full text |Cite
|
Sign up to set email alerts
|

Screening of seed lipids for γ‐linolenic acid: Capillary gas‐liquid chromatographic separation of 18:3 fatty acids with Δ5 and Δ6 double bonds

Abstract: y-Linolenic acid (6c,9c, 12c-18:3) has recently become important for dietary and pharmaceutical applications. The reported occurrence of y-linolenic acid in seed oils from plant families known to produce fatty acids, including 18:3 acids, with AS-cis and AS-trans double bonds makes it necessary to distinguish between Sc,9c,12c-, St,9c,12c-and 6~,9~,12~-octadecatrienoic acids by gas chromatography (CC) alone in routine screening operations. The separation of these acids using two different capillary GC systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…It must also be mentioned that the separation characteristics of two columns of the same type can demonstrate slight variations from charge to charge and even different elution orders, e.g. for Silar 5CP columns were reported [124]. A recent paper from Stransky et al [134] demonstrated that the accuracy of the ECL values depends also on the method of calculation and the same authors proposed in a following work [132] that the linear dependence of the ECL values on the number of carbons should be substituted by a higher order polynomial to obtain more accurate results.…”
Section: Capillary Columnmentioning
confidence: 98%
See 1 more Smart Citation
“…It must also be mentioned that the separation characteristics of two columns of the same type can demonstrate slight variations from charge to charge and even different elution orders, e.g. for Silar 5CP columns were reported [124]. A recent paper from Stransky et al [134] demonstrated that the accuracy of the ECL values depends also on the method of calculation and the same authors proposed in a following work [132] that the linear dependence of the ECL values on the number of carbons should be substituted by a higher order polynomial to obtain more accurate results.…”
Section: Capillary Columnmentioning
confidence: 98%
“…BPX-70 TM ∆5-unsaturated polymethylene-interrupted fatty acids in Ranunculaceae [120]; γ-linolenic, α-linolenic, and stearidonic acid in Boraginaceae [121]; acetylenic fatty acids in Olacaceae [11] Carbowax 20M TM /DB Wax TM Conjugated triene fatty acids in Cucurbitaceae [90], positional monoene isomers in Sapindaceae [2,122], ∆5-unsaturated polymethylene-interrupted fatty acids in Cupressaceae, Pinaceae, and Taxaceae [123] CP-SIL-88 TM Unusual unsaturated double bond and configuration isomers in Ranunculaceae [124] and Pinaceae [125] CP-WAX 52CB TM Methyl-branched and ∆5-unsaturated polymethylene-interrupted fatty acids in Ginkgo biloba [20] DB-23 TM Cyclopropanoic, cyclopropenoic, and hydroxy fatty acids in Bombacaceae [14], positional monoene isomers in Sapindaceae [2,122], conjugated triene, tetraene, and keto fatty acids in Chrysobalanaceae [21,77,126] and Euphorbiaceae [6], acetylenic acids in Olacaceae [3,128] and Santalaceae [3,128] SILAR 5 CP TM ∆5-unsaturated polymethylene-interrupted fatty acids in Ranunculaceae [129], allenic fatty acids [13] SP2330 TM Polyunsaturated fatty acids in various species [130] Detection of the individual compounds can be made with a flame-ionization detector (FID).…”
Section: Capillary Columnmentioning
confidence: 99%
“…Capillary gas-liquid chromatography (GLC) on columns of different selectivity is a powerful analytical tool to detect and identify γ-Ln and other unusual positional or geometrical isomers of fatty acids that occur as seed oil components (21)(22)(23)(24). However, some care is needed in investigations of Compositae seed oils, because other 18:3 fatty acid isomers may be present.…”
mentioning
confidence: 99%
“…Sterols were recrystallized from methanol. Acylglycerols were hydrolyzed using KOH (5.6%) in ethanol calculated as alkaline solution (10 mL) per TAG (0.2-0.25 g) with stirring for 30 min [9]. FA were methylated using CH 2 N 2 in Et 2 O. Diazomethane was produced as before [11].…”
Section: Methodsmentioning
confidence: 99%
“…Their composition was determined by GC of the methyl esters [7][8][9][10]. Table 1 shows that NL of the studied seeds had a FA composition consisting of only 5-6 components.…”
Section: 915mentioning
confidence: 99%